MELEK MEDIA DALAM MENGELIMINIR DAMPAK TELEVISI PADA ANAK - Firman Alamsyah Taufik Robbi (Dialektika, 2016)
Media literacy will not be balanced, when the broadcast media as producers are not encouraged to become an institution that is "healthy". For the parallel suggested steps to eliminate the negative impact. Commitment, a sincere intention to make the media as a medium of learning, to educate the audience and think about the impact. Professionalism is valued media owners (reward and punishment) and have extensive knowledge, creativity, sophistication of taste. System, rules and ethics of a healthy broadcast industry; clear and enforced. Packaging exciting educational broadcasts, preferably involving the audience with visual communication experts, education experts, psychologists etc. and based on research. Make broadcast 'educational entertainment' or press 'education entertaining'. Open up opportunities and access for every group of people who are interested.